Urokinase-type Plasminogen Activator and Plasminogen Activator Inhibitor Induction by Etoposide in a Glioblastoma Cell Strain - Branko Brdar; Maja Matulić (Food Technology and Biotechnology, 2002)
Urokinase plasminogen activator (uPA) and its inhibitors (PAI) are elements of plasminogen activation system, a proteolytic system involved in many physiological and patological processes. In this paper their induction by etoposide, a topoisomerase II inhibitor, in A1235 glioblastoma cell strain is described. Etoposide induced uPA and PAI production, in a dose- and time-dependent manner. Induction was based on the activation of their promoters and extracellular proteolysis was dependent on their equilibrium. Etoposide caused p53 activation and p21 and gadd45 induction, which could be responsible for the cell growth arrest. Our data indicate that several pathways could be involved in the uPA and PAI induction.